Faraday’s Laws and the Flipped Classroom: A proposal for distance learning (Research, Society and Development, 2021)
The present article describes a proposal for teaching Faraday’s Laws, within electrolysis content, using the Flipped Classroom methodology. This proposal was developed in completely distance learning lessons, in Chemistry, with two High School classes in the third year. In addition, this article conducts a bibliographic mapping of the presence of previous works with the methodology and contents discussed. The mapping of articles was important to reveal a gap in the literature regarding the presence of studies involving Faraday’s Laws and the Flipped Classroom. With the absence of previous articles, this article developed a pioneering proposal in the field, where the Flipped Classroom highlighted the development of conceptual contents about Faraday’s Laws and stimulated the active participation of students in distance learning. Finally, with the work developed, the potential of the Flipped Classroom as a methodology to be used in Chemistry Teaching was noted, mainly in the teaching of Faraday’s Laws in electrochemistry.